A comparative analysis of game theory techniques for study of energy interactions in interconnected microgrids. (16th November 2021) - Zeeshan, Mohammad; Jamil, Majid
The growing energy needs of society can be met with one or more microgrids working in conjunction. A need of a trading and scheduling mechanism for energy exchange among microgrids for sustainable development of the consumers is required. Game theory techniques have been widely utilised to study this interaction among microgrids. This paper seeks to analyse the different game theory-based energy trading techniques to elaborate on such models' efficiencies. The study is based on renewable energy generation and consumption in Denmark. Lexicographic egalitarian solution is proposed as a bargaining solution for two participating microgrids in an energy trading game. A comparison is performed between the proposed model and conventional techniques for inter-microgrid trading. The proposed bargaining solution depicts a fairness index of 0.974 compared to 0.946 for the Nash solution and 0.954 for the Kalai-Smorodinsky solution. The results of the proposed study provide a better insight into the various aspects of energy sharing algorithms and will help improve the utilisation of green energy.